Desenvolvimento e caracterização de tecidos vítreos flexíveis altamente bioativos - Souza, Marina Trevelin (Universidade Federal de São Carlos, 2015)
Bioactive glasses were developed by Hench in 1969, and are widely known to have the ability to rapidly form a chemical bond with hard and soft living tissues. Currently, these glasses have been used clinically as biomaterials that act in bone regeneration in dental and orthopedic applications. However, their use is still very limited due to their fragility and also the limited commercially available forms, such as powders and granules. Therefore, the development of processes that make possible their conformation in fibers and fabrics (meshes) is indeed promising and highly desired, as this new shape could significantly expand the usage spectrum of this excellent biomaterial. Thus, this project aimed to develop and improve the production of highly bioactive glass fibers by the downdrawing process, as well as optimize the production of unwoven fabrics and characterize them in relation to their physicochemical and biological properties. Therefore, a new bioactive glass composition previously developed at the Vitreous Materials Laboratory was used (LaMaV - UFSCar). This new bioactive glass presents a fast interaction with the body fluids to rapidly promote the healing process and reduced crystallization tendency for its processing into fibers, as crystal formation difficult or even impossible to obtain the same. The obtained results showed that this new bioactive glass composition is more suitable to undergo through working processes involving high temperatures than other currently known bioactive glasses, being then, possible to produce highly flexible fabrics and meshes by the downdrawing process. Concurrently, this new biomaterial presents similar physical-chemical and biological properties to gold standard bioglass 45S5, making this new biomaterial suitable for several applications aiming in situ tissue regeneration.
Development and characterization of flexible and highly bioactive glass fibers meshes
Keywords: Vidros; Vidro bioativo; Fibra de vidro bioativo; Regeneração tecidual; Engenharia de tecidos; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA::MODELAGEM DE SISTEMAS BIOLOGICOS; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA